Viabilidade agronômica do consórcio de alface e rúcula, em duas épocas de cultivo - Costa, Caciana Cavalcanti; Cecílio Filho, Arthur Bernardes [UNESP]; Rezende, Bráulio Luciano Alves; Barbosa, José Carlos [UNESP]; Grangeiro, Leilson Costa (Associação Brasileira de Horticultura, 2007)
Avaliou-se a produtividade de grupos de alface e da rúcula, em consórcio, em relação aos seus cultivos solteiros, na UNESP Jaboticabal, em condições de campo, em duas épocas de cultivo, maio a agosto e setembro a novembro de 2001, sob delineamento de blocos casualizados, com quatro repetições. Os tratamentos constaram de combinações dos fatores grupos de alface (crespa, cv. Vera; lisa, cv. Elisa e americana, cv. Tainá), sistemas de cultivo (consórcio e cultivo solteiro) e épocas de semeadura da rúcula para o estabelecimento do consórcio [0; 7 e 14 dias após o transplante (DAT) da alface]. As maiores matérias fresca e seca de alface foram obtidas na primavera, com destaque para a alface americana. As alfaces não foram afetadas pelo sistema de cultivo. A maior matéria fresca de rúcula, no outono-inverno, foi obtida em consórcio, a 0 DAT, com as alfaces crespa e lisa e, aos 7 DAT com americana, enquanto na primavera, quando foi consorciada aos 7 DAT com alface crespa e a 0 DAT com alfaces do grupo lisa e americana. A rúcula teve sua matéria seca reduzida nos consórcios estabelecidos tardiamente, aos 14 DAT. Os cultivos consorciados apresentaram-se superiores aos cultivos solteiros entre 5 e 93%, segundo o índice de uso eficiente da terra. Os maiores índices de uso eficiente da terra foram obtidos com os consórcios de rúcula e alface crespa a 0 DAT (1,93), no outono-inverno e pelas mesmas hortaliças aos 7 DAT (1,84), na primavera.

The productivity of different lettuce groups and roquette was evaluated when sown in two different periods and cultivated either singly or intercropped. Theses experiments were carried out in Jaboticabal, São Paulo State, Brazil. The first growing period was from May to August (Autumn-Winter) and the second from September to November (Spring) of 2001. The experimental design was a randomized complete block with four replications. The treatments consisted of the combination of the following factors levels: lettuce groups (crisp, cv. Vera; looseleaf, cv. Elisa; and crisphead lettuce, cv. Tainá), cropping systems (intercropping and sole crop) and roquette sowing times [0; 7, and 14 days after lettuce transplantating (DAT)]. The highest fresh and dry matter production were observed for crisphead lettuce in the Spring. The cropping systems did not affect the lettuce groups productivity. The highest roquette fresh matter production was observed in the Autumn-Winter period at 0 DAT, with the crisp and looseleaf lettuce, and at 7 DAT with crisphead lettuce. For the Spring period the highest roquette fresh matter production was observed at 7 DAT with crisp lettuce and at 0 DAT with looseleaf and the crisphead lettuce. Roquette dry matter was reduced in the intercropping at 14 DAT. The intercropping system yielded 5 to 93% more than the single system according to the land equivalent ratio. The highest land equivalent ratio was observed in the roquette-crisp lettuce intercropping at 0 DAT the crisp variety (1.93) in the Autumn-Winter, while the highest ratio was observed at 7 DAT (1.84) in the Spring.
Agronomic viability of lettuce-roquette intercropping in two growing periods
Keywords: Lactuca sativa; Eruca sativa; cropping system; land equivalent ratio; Productivity; intercropping; Lactuca sativa; Eruca sativa; Sistema de cultivo; uso eficiente da terra; Produtividade; consorciação